2014
DOI: 10.1177/0148558x14530129
|View full text |Cite
|
Sign up to set email alerts
|

Investors’ Reactions to Analysts’ Forecast Revisions and Information Uncertainty

Abstract: This study examines the relationship among analysts’ earnings forecast revisions, information uncertainty, and stock returns and provides new evidence that stock price drift occurs after analysts’ earnings forecast revisions. Using data from the Australian stock market over the period of 1992 to 2009, we find that the stocks with upward earnings revisions experience positive returns, while stocks with downward revisions have negative returns. The effect is more prominent in stocks with high information uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…This is evidenced in many existing literatures as well. For example, the study performed by Hou et al (2014) revealed that positive earnings forecast together with positive upgrade on earning forecast built investors' confidence towards a firm's stock performance, subsequently leading to a positive gain. This finding is also consistent with Fama (1984) and Ali et al (1992).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This is evidenced in many existing literatures as well. For example, the study performed by Hou et al (2014) revealed that positive earnings forecast together with positive upgrade on earning forecast built investors' confidence towards a firm's stock performance, subsequently leading to a positive gain. This finding is also consistent with Fama (1984) and Ali et al (1992).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Return on assets (ROA) ratio also indicates the level of company's performance (Purnamasari 2015). Ball and Brown (1968), Hou et al (2014) indicate that in addition to the mentioned financial ratios, earning per share ratio (EPS) may serve as a variable when forecasting stock prices. Analysts estimate that the stock price increases when reported ratio is higher than expected and vice versa -if it is lower, then the stock price decreases (Renfro 2015).…”
Section: Review Of Theoretical Stock Price Forecast Methods and Modelsmentioning
confidence: 99%
“…Dische and Zimmerman (1999) demonstrate that trading portfolios formed based on analyst forecast revisions could generate a cumulative abnormal return (CAR) of 14% in the Swiss market. In the Asia‐Pacific markets, Aitken, Frino, and Winn (1996) and Hou, Hung, and Gao (2014) document a positive association between analyst forecast revisions and stock returns using Australian stock market data in the period 1985–1992 and the period 1992–2009 respectively. Lim and Kong (2004) also obtain results of a positive association between analyst forecast revision and future abnormal returns in Australia as well as three other Asia‐Pacific markets: Hong Kong, Korea and Singapore.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%